Forest Cover Dynamics in the City of Poznań from 1830 to 2004 - Macias, Andrzej; Dryjer, Marta (Quaestiones Geographicae, 2010)
Forests on the urban areas are of a great importance for the biodiversity of this territory. Moreover, they play numerous functions in the environment and constitute, at present, on important element of the ecological urban system. Nevertheless, the changes of the forest areas in the city of Poznań have never been discussed so far. This article presents the results of research of the changes of forest areas in Poznań within the administrative borders of Poznań in 2004. It was performed for the period 1830-2004 for six selected moments in which topographic maps of this area were prepared i.e. 1830, 1888, 1940, 1960, 1979 and 2004 During this period forest area increased by 2367 ha. The effect of numerous afforestations and deforestations is that forest area which was not subject to these treatments from 1830 to 2004 constitutes only 481 ha (14.6% of forest areas of Poznań). Four periods of dynamics of changes of forest areas were distinguished. During the last one, taking place presently, forest area has decreased slightly. In the case of Poznań, maintaining forests is significant from the point of view of their importance not only for functioning of green wedges but also the whole environment of this city. Therefore, one of the directions of spatial development of the city of Poznań should be maintaining and increasing forest areas as the element of the implementation of sustainable development principles.